Sempronia, Q. Curius, and the Decline of Roman Gentes in Sallust’s Bellum Catilinae - Loar, Matthew (Histos, 2019)
In the Bellum Catilinae, Sallust includes detailed character sketches of two Catilinarian conspirators: Q. Curius and Sempronia. Based on a number of lexical and syntactical similarities between the two sketches, this article proposes interpreting them as a matched pair, one that provides a narrative pendant to the earlier pairing of Sallust and Catiline. The article then argues that Sallust singles out Curius and Sempronia as compelling exemplars of the conspiracy because they (and Curius’ mistress Fulvia) synecdochally symbolise the downfall of three Roman gentes—a downfall that was already visible in the recent renaming of the Basilicas Sempronia and Fulvia.